2016
DOI: 10.18632/oncotarget.9559
|View full text |Cite
|
Sign up to set email alerts
|

BKCa promotes growth and metastasis of prostate cancer through facilitating the coupling between αvβ3 integrin and FAK

Abstract: BKCa is a large conductance calcium activated potassium channel promoting prostate cancer cell proliferation, although the mechanism is not fully elucidated. In addition, whether BKCa is involved in metastasis of prostate cancer remains to be explored. Here, we report that BKCa is overexpressed in prostate cancer. BKCa expression positively correlates with Ki67 index and gleason score of prostate cancer. Upregulation of BKCa promoted proliferation, migration and invasion of prostate cancer cells. On the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…In other cell types, KCNMA1 activation can protect cardiomyoblast cells from hypoxia/reperfusion damage (Fretwell and Dickenson, 2011) and reduce shock-induced reductions in vascular reactivity (Hu et al, 2014). KCNMA1 channel activity can also facilitate prostate cancer cell growth possibly through an association with avb3 integrin and focal adhesion kinase (Du et al, 2016). Although the absence of potassium channel function may explain the elevated intracellular calcium in AS1 (and AS2) podocyte-like cells, the mechanism underlying this effect was not immediately clear.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, KCNMA1 activation can protect cardiomyoblast cells from hypoxia/reperfusion damage (Fretwell and Dickenson, 2011) and reduce shock-induced reductions in vascular reactivity (Hu et al, 2014). KCNMA1 channel activity can also facilitate prostate cancer cell growth possibly through an association with avb3 integrin and focal adhesion kinase (Du et al, 2016). Although the absence of potassium channel function may explain the elevated intracellular calcium in AS1 (and AS2) podocyte-like cells, the mechanism underlying this effect was not immediately clear.…”
Section: Discussionmentioning
confidence: 99%
“…FAK is overexpressed in several tumor types and is believed to play a role in tumor progression and metastasis . Therefore, FAK is discussed as an effective cancer target in various tumors …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Therefore, FAK is discussed as an effective cancer target in various tumors. [13][14][15][16][17] To our knowledge, there are no data on the association between THSD7A and human cancer. The demonstrated association between a malignant tumor and the development of MN raised the question whether THSD7A had been involved in the tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting metastatic breast cancer cells in brain is extremely difficult as brain provides a "safe haven" for cancer cells. Gene expression profiling has been used to predict metastatic gene-expression signature that is present in a subset of primary breast tumors [8]. However, a reliable profile has not yet been identified that specifically predicts brain metastases.…”
Section: Metastatic Breast Cancer Etiologymentioning
confidence: 99%
“…Activation of BK Ca channels was shown to be a novel molecular pathway involved in zoledronic acidinduced apoptosis of MDA-MB-231 cells in vitro [32]. Du et al [8] showed that BK Ca promotes growth and metastasis of prostate cancer through facilitating the coupling between αvβ3 integrin and FAK. BK Ca channels are shown to support cancer cell migration, invasion and tumorigenesis [11,17,18].…”
Section: Bk Ca Channels As Target To Attenuate Breast Cancer Metastasismentioning
confidence: 99%